2018
DOI: 10.3390/molecules23102723
|View full text |Cite
|
Sign up to set email alerts
|

Nuciferine Inhibits Proinflammatory Cytokines via the PPARs in LPS-Induced RAW264.7 Cells

Abstract: Inflammation is important and has been found to be an underlying cause in many acute and chronic human diseases. Nuciferine, a natural alkaloid containing an aromatic ring, is found in the nelumbo nucifera leaves. It has been shown to have potential anti-inflammatory activities, but the molecular mechanism has remained unclear. In this study, we found that nuciferine (10 μM) significantly inhibited the lipopolysaccharide (LPS)-induced inflammatory cytokine IL-6 and TNF-α production in RAW 264.7 cells. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…All sacred lotus parts contain high bioactive compounds, and have been used for pharmacological purposes such as anti-oxidative, astringent, emollient, diuretic [ 6 ], anti-diabetic [ 8 ], anti-hyperlipidemic [ 9 ], anti-aging [ 6 , 10 ], anti-ischaemia [ 11 ], anti-viral [ 12 ], anti-inflammatory [ 13 , 14 ], anti-allergic [ 15 ], anti-cancer [ 16 ], and hepatoprotective effects [ 17 ]. Interestingly, sacred lotus extracts were also previously reported to affect neurodegenerative disorders, especially Alzheimer’s disease (AD) [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…All sacred lotus parts contain high bioactive compounds, and have been used for pharmacological purposes such as anti-oxidative, astringent, emollient, diuretic [ 6 ], anti-diabetic [ 8 ], anti-hyperlipidemic [ 9 ], anti-aging [ 6 , 10 ], anti-ischaemia [ 11 ], anti-viral [ 12 ], anti-inflammatory [ 13 , 14 ], anti-allergic [ 15 ], anti-cancer [ 16 ], and hepatoprotective effects [ 17 ]. Interestingly, sacred lotus extracts were also previously reported to affect neurodegenerative disorders, especially Alzheimer’s disease (AD) [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the effects of the so-called PPAR antagonists themselves. Indeed, in relation to the cells of macrophage origin (RAW 264.7), all three PPAR subtype antagonists (GW5417; GSK0660; GW9662) increased TNFα synthesis by 12 h in the LPS-stimulated cells [ 67 ]. We identified that GSK0660 and GW9662 inhibited TNFα synthesis by 6 h on LPS-stimulated astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Many powerful chemotherapy drugs such as doxorubicin, teniposide, and etoposide are topoisomerase II inhibitors [205]. However, serious side effects could result from using these drugs due to the lack of selectivity as well as the risk of drug resistance due to the enzymes' gene mutation or dysregulation of their expression in tumor cells [194,[207][208][209]. Thus, looking for new phytochemicals that targeting topoisomerases enzyme is a promising branch in chemotherapy development.…”
Section: Topoisomerasesmentioning
confidence: 99%
“…On the other hand, resveratrol repressed the hypoxia-induced resistance to doxorubicin in MCF-7 cells via downregulation of HIF-1α protein expression [208]. Nuciferine is an aromatic alkaloid extracted from lotus leaves that exhibited anti-inflammatory, antioxidant, and anticancer properties [209,233,234]. Recently, nuciferine has been applied in drug-resistant tumor cells, and it was able to regulate MDR proteins as well as reduce the activation of Nrf2 and HIF-1α [235].…”
Section: Hypoxia-inducible Factormentioning
confidence: 99%